A corrosão das armaduras nas estruturas de concreto armado em edificações da primeira metade do século XX: uma metolologia para sua detecção - Isaia, Gustavo de Aguiar (2010)
The corrosion study in actual concrete structures is a subject enough discussed as much in the academic ambience as in the professional one. The subject is relevant due the numberless pathology cases of corrosion in structural concrete that are reported, almost daily, in the technical sphere. Nevertheless, few are the studies on this phenomenon in structural concrete of the first half of the 20th century. Is common sense that these structures were executed in a different way from the actual, and its behavior in front of corrosion may be differentiated, however, little are the studies that analyze the behavior of these structures in front of this pathology. This dissertation, based on bibliographical study and author s experience, look for not only analyze the concrete structure characteristics of the first half of 20th century and its influence on the rebar corrosion, as also propose a methodology for its detection. The proposition of this theme is based in fact that many execution and calculus methods were enough different from the actual concerning the concrete structures. The sodium chloride and calcium chloride addition in concrete, with purpose to accelerate the set and curing of concrete, the use of wooden pins as spacers are some characteristics showed in this work. As conclusion, is proposed an evaluation methodology which permits analyze such structures under the optics of its peculiar characteristics, aiming at the rebar corrosion.